Willingness to participate in a lifestyle intervention program of patients with type 2 diabetes mellitus: a conjoint analysis - van Gils, Paul F (Dove Medical Press, 2011)
BACKGROUND: Several studies suggest that lifestyle interventions can be effective for people with, or at risk for, diabetes. The participation in lifestyle interventions is generally low. Financial incentives may encourage participation in lifestyle intervention programs. OBJECTIVE: The main aim of this exploratory analysis is to study empirically potential effects of financial incentives on diabetes patients’ willingness to participate in lifestyle interventions. One financial incentive is negative (“copayment”) and the other incentive is positive (“bonus”). The key part of this research is to contrast both incentives. The second aim is to investigate the factors that influence participation in a lifestyle intervention program. METHODS: Conjoint analysis techniques were used to empirically identify factors that influence willingness to participate in a lifestyle intervention. For this purpose diabetic patients received a questionnaire with descriptions of various forms of hypothetical lifestyle interventions. They were asked if they would be willing to participate in these hypothetical programs. RESULTS: In total, 174 observations were rated by 46 respondents. Analysis showed that money was an important factor independently associated with respondents’ willingness to participate. Receiving a bonus seemed to be associated with a higher willingness to participate, but having to pay was negatively associated with participation in the lifestyle intervention. CONCLUSION: Conjoint analysis results suggest that financial considerations may influence willingness to participate in lifestyle intervention programs. Financial disincentives in the form of copayments might discourage participation. Although the positive impact of bonuses is smaller than the negative impact of copayments, bonuses could still be used to encourage willingness to participate.